Factors affecting the performance of construction projects in the Gaza strip - Enshassi, Adnan; Mohamed, Sherif; Abushaban, Saleh (Journal of Civil Engineering and Management, 2009)
Construction projects located in the Gaza Strip, Palestine suffer from many problems and complex issues. Consequently, the objective of this paper is to identify the factors affecting the performance of local construction projects; and to elicit perceptions of their relative importance. A comprehensive literature review was deployed to generate a set of factors believed to affect project performance. A total of 120 questionnaires were distributed to 3 key groups of project participants; namely owners, consultants and contractors. The survey findings indicate that all 3 groups agree that the most important factors affecting project performance are: delays because of borders/roads closure leading to materials shortage; unavailability of resources; low level of project leadership skills; escalation of material prices; unavailability of highly experienced and qualified personnel; and poor quality of available equipment and raw materials. Based on these findings, the paper recommends that: 1) project owners must work collaboratively with contractors and facilitate regular payments in order to overcome delays, disputes and claims; 2) project participants should actively have their input in the process of decision‐making; and 3) continuous coordination and relationship between project participants are required through the project life cycle in order to solve problems and develop project performance. Santrauka Statybos projektai Gazos Ruože, Palestinoje, kenčia nuo daugelio problemų ir sudėtingų klausimų. Todėl pagrindinis šio straipsnio tikslas yra nustatyti veiksnius, darančius įtaką vietos statybos projektams įgyvendinti, ugdyti suvokimą apie jų santykinę svarbą. Iš viso 120 respondentų buvo suskirstyti į tris pagrindines projektų dalyvių grupes: savininkai, konsultantai ir rangovai. Apklausa parodė, kad visos trys grupės sutinka, kad svarbiausi veiksniai, lemiantys projekto įgyvendinimą, yra: atidėliojimas, susijęs su sienų (kelių) uždarymu ir lemiantis medžiagų stygių; negaunamos atsargos; menki vadovavimo projektams įgūdžiai; nepagrįsta medžiagų kaina; patyrusio ir kvalifikuoto personalo stoka ir prasta įrankių ir žaliavos kokybė. Pasitelkiant šias išvadas, straipsnyje rekomenduojama: 1) projektų savininkai turi dirbti kartu su rangovais ir reguliariai atsiskaityti norėdami išvengti atidėliojimų, ginčų ir pretenzijų; 2) projekto dalyviai turėtų aktyviai dalyvauti priimant spendimus; 3) nuolatinė projekto dalyvių kontrolė ir jų tarpusavio santykis yra reikalingi per visą projekto įgyvendinimo ciklą norint išspręsti iškilusias problemas ir įgyvendinti projektą. Reikšminiai žodžiai: įgyvendinimas, savininkai, konsultantai, rangovai, projektai.